Analisis Penerapan Artificial Intelligence dalam Sistem Pembelajaran Cerdas: Kajian Literatur - Elsa Sabrina; Fadilla; Rifki Ferdiansyah; Patra AdyPratama; Muhammad Nadhif Faturrahman; Marissa Dealova Marbun (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2025)
The development of Artificial Intelligence (AI) has increasingly influenced various aspects of life, including the field of education. In learning processes, AI functions as a system capable of analyzing data, providing learning recommendations, and adapting materials to students’ needs. This literature review aims to describe the application of AI in intelligent learning systems and the benefits it brings to teaching and learning activities. The method used is a literature study based on relevant national and international journals published within the last five years. The findings indicate that AI implementation can enhance learning personalization, improve assessment effectiveness, and support teachers in making data-driven decisions. However, its implementation still faces challenges, such as limited infrastructure, low digital literacy, and teachers’ readiness to operate the technology. Therefore, AI holds significant potential to support adaptive and efficient learning, yet it requires improved teacher competencies and adequate facilities to maximize its application.